Evidence that Maternal Age Influences the Occurrence of Optic Nerve Hypoplasia. (July 2018) - Ivy, Sarah E.; Hatton, Deborah D.
Introduction: This study evaluated the influence of maternal age on the presence of optic nerve hypoplasia. Methods: Logistic regression analysis was used to find the best-fit model to explain the presence of optic nerve hypoplasia (ONH), and to estimate the unique variance accounted for by maternal age, in a sample of 4, 269 children with severe visual impairments who entered early intervention programs in the United States between 2004 and 2010. Results: Maternal age, birth weight of infant, and gestational age were found to be significant predictors of ONH compared to other visual conditions. Maternal age was found to be negatively associated with the probability of having ONH in this sample. Discussion: Findings are consistent with previous reports of increased incidence of ONH in children born to young mothers (Garcia-Filion, Fink, Geffner, & Borchert, 2010; Tornqvist, Ericsson, & Källén, 2002). Implications for practitioners: Early interventionists, social workers, and health professionals working with young mothers of children with severe visual impairments should be aware of the dangers and warning signs of associated endocrinopathies, and should encourage at-risk families to discuss this with their pediatrician.